Analisis Pengaruh Budaya Organisasi Terhadap Kinerja Anggota Kepolisian Resort Malang - Sani, Achmad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2004)
The study aims at: 1) describing the organization culture and performance, 2) finding out the simultaneuos influence of organization culture (variables of innovation, reward, cooperation or team work, result or outcome orientation and service orientation) on the performance. This is an explanatory research involving the employees of Polresta Malang as the analysis unit. The studi used proportional random sampling method and to collect data from 81 respondent a questionnaire was used The analysis technique used were multiple, partial regression, and determination. The result of study showed that: 1) simultaneously the organizational culture significantly influenced the performance, 2) partial(v the organization culture had also positive influence on the performance, 3) reward had the most significant influence on the performance. Based on the finding, therefore it is suggested that the organization pays more attention to reward, either material reward or non material reward, since reward is basically a dominant variable in influencing performance.